2018
DOI: 10.1186/s12884-018-1838-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors associated with sexual health issues in primiparous women at 6 and 12 months postpartum; a longitudinal prospective cohort study (the MAMMI study)

Abstract: BackgroundMany women are not prepared for changes to their sexual health after childbirth. The aim of this paper is to report on the prevalence of and the potential risk factors (pre-pregnancy dyspareunia, mode of birth, perineal trauma and breastfeeding) for sexual health issues (dyspareunia, lack of vaginal lubrication and a loss of interest in sexual activity) at 6 and 12 months postpartum.MethodsA longitudinal cohort study of 832 first-time mothers who were recruited in early pregnancy and returned postnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
5
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 33 publications
(40 reference statements)
9
85
5
7
Order By: Relevance
“…For others, they helped them realize they had a health problem, and prompted them to take better care of themselves or seek professional help, even up to 12 months postpartum. Contrary to previously held beliefs that women's bodies return to their pre‐pregnant state within 6 weeks postpartum, findings from this and other studies show that some health problems are present before women's first pregnancy, that considerable proportions of women experience persistent and long‐term morbidities and that some women's health can deteriorate during the year after giving birth. A systematic review of morbidities experienced by women who had a postpartum haemorrhage found that women who suffered problems such as coagulopathy [a disorder affecting the blood's ability to clot] (1.74 %), post‐traumatic stress disorder (3%), or required readmission to hospital 1‐3 months postpartum (3.6 %) described their health as “much worse than 1 year ago” (6%) .…”
Section: Discussioncontrasting
confidence: 99%
“…For others, they helped them realize they had a health problem, and prompted them to take better care of themselves or seek professional help, even up to 12 months postpartum. Contrary to previously held beliefs that women's bodies return to their pre‐pregnant state within 6 weeks postpartum, findings from this and other studies show that some health problems are present before women's first pregnancy, that considerable proportions of women experience persistent and long‐term morbidities and that some women's health can deteriorate during the year after giving birth. A systematic review of morbidities experienced by women who had a postpartum haemorrhage found that women who suffered problems such as coagulopathy [a disorder affecting the blood's ability to clot] (1.74 %), post‐traumatic stress disorder (3%), or required readmission to hospital 1‐3 months postpartum (3.6 %) described their health as “much worse than 1 year ago” (6%) .…”
Section: Discussioncontrasting
confidence: 99%
“…The reported incidence does not include many other health problems that are common during pregnancy and postpartum, such as depression, incontinence, sexual health issues, and pelvic girdle pain. [2][3][4][5][6] These types of health problems are frequently underreported and undertreated, due to their sensitive nature, or a belief that they are normal, selflimiting symptoms of pregnancy and birth. [7][8][9] There is a growing body of research describing their prevalence, which indicates that almost all women (94%) experience at least one major health problem in the first year after having a baby, with up to one in five (20%) reporting depressive symptoms and almost half (47%) reporting urinary incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…Although the women did not feel rejected by their partners, their dissatisfaction with their physical appearance resulted in them feeling less intimate and less confident about returning to sexual activity. Similarly, O'Malley et al [56] found positive selfimage improves sexual health, including the woman's satisfaction with intercourse in the postpartum.…”
Section: Discussionmentioning
confidence: 93%
“…[8] For women in varied contexts, unique cultures and different countries, dynamic changes in the postpartum negatively impact their sexual desire as well as satisfaction [32][33][34][35][36][37][38][39][40][41][42][43][44], and even stimulates fear. [45] Researchers, primarily from economically developed countries, have reported a variety of issues that impact the overall experience of women when returning to sexual activity, including: dyspareunia [22,32,35,37,41,[46][47][48][49][50][51][52], decreased libido [51,[53][54][55], problems achieving orgasm [11,46,48,56], negative body image [33,53,54], fatigue and sleep deprivation [53][54][55]57], relationship satisfaction [43,57], household responsibilities [54], and concerns about satisfying partner.…”
Section: Sexual Health and Womenmentioning
confidence: 99%
See 1 more Smart Citation